Institucionalização escolar e empreendedorismo: efeitos da governamentalidade neoliberal na sujeição do aluno a EJA - Souto, Elize de Matos (2014)
This dissertation aims at problematizing the effects of neoliberal governmentality on the conduction of subjects in contemporaneity, in a society that has been produced by the security logic. By proposing such investigative endeavor, this study focuses on the school and regards it as one of the most potent locus of production of subjects aligned to the State. Thus, the objective of this research is to understand the effects of neoliberal governmentality on the production of contemporary subjects by considering the alliance between State and school. In order to achieve such objective, five Youth and Adult Education (EJA) students were interviewed. EJA is understood as a practice that gives visibility to governmentality. The recurrences found in those subjects narratives, through the genealogical inspiration by Michel Foucault, triggered a search for the conditions of existence that have enabled the emergence of such discourses, thus constituting them as truths, delineating and producing subjects in contemporaneity. The analysis of recurrences found in the narrative interviews allowed the identification the following utterances: the need to be institutionalized in the school context, and the need to become a self entrepreneur. In order to look at such materials, the concept of governmentality developed by Michel Foucault was used. From this perspective,it was noticed that institutionalization, by means of education, has been understood as a salvation practice that has been developing throughout history, making the subjects be captured and have their conducts conducted to meet the State requirements at every historical moment, thus showing the potency of truth on the school operating even when the subject is not linked to that institution. The same can be said of entrepreneurship, which, since industrialization, has used education as a vehicle for the subjectivation of subjects able to invest in themselves, manage their lives and risks by means of incessant searches for better life conditions, which involve being able to consume and participate in contemporaneity. At the end of the research, although the focus of investigation was EJA, it was possible to understand that such education modality, as well as special education, quilombo education and distance education, among others, has been affected by the imperative of truth that has pointed out inclusion, developed through the neoliberalism logic, to capture every subject and constitute them as the target of current government technologies.